Labor Market Institutions and Unemployment Dynamics in Transition Economies - Garibaldi, Pietro (IMF Working Papers; Working Paper, 1997)
This paper studies interactions between labor market institutions and unemployment dynamics in transition economies. It presents a dynamic matching model in which state sector firms endogenously shed labor and private job creation takes time. Two main conclusions arises. First, higher unemployment benefits increase steady-state unemployment, and, during the transition, they reduce the fall in real wages and speed up closure of state enterprises. Second, higher minimum wages can theoretically speed up the elimination of state sector jobs without affecting steady-state unemployment. These results are broadly consistent with existing evidence on the dynamics of unemployment and real wages in transition economies.